Effects of Different Types of Pinching in Growth and Yield of Two Varieties of Okra (Abelmoschus esculentus L.) in Pokhara, Kaski, Nepal - Prajjwal Koirala; Rijwan Sai; Pratikshya Subedi; Chiranjibi Khadka (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted in Pokhara, Kaski, Nepal in 2023 to investigate the effects of different pinching types and okra varieties on various growth and yield parameters. Treatments were arranged under a two-factor Randomized Complete Block Design (RCBD) with three replications. The treatments includes two okra varieties (Arka Anamika and Parbati) and 4 pinching types (apical bud pinching (P1), ABP along with 1 leaf pinching (P2), and ABP along with 2 leaf pinching (P3) and control (P4)). Parbati has exhibited a higher plant height (80.78 cm) than Arka Anamika (72.35 cm). Similarly, the P4 pinching type resulted in the tallest plant (85.91 cm). The P1 pinching type demonstrated the highest number of primary branches (4.87), while the control plots had the lowest (3.00). Arka Anamika showed a higher leaf count (40.77) than Parbati (37.19). Notably, the P1 recorded the highest leaf count (43.41), followed by P2 (37.19), with the control plots showing the lowest leaf count (32.76). The findings reveal the significant impact of pinching treatments on yield. Pinching type P1 produced the highest yield of 15.45 mt/ha, whereas the control group yielded the lowest at 9.31 mt/ha, which was comparable to the yield observed for pinching type P3 at 10.83 mt ha-1. P1 also exhibited the highest number of pods per plant (15.90). Varieties and pinching methods exhibited notable interactions in average pod weight, diameter, and length. P1 displayed the widest pods (5.97 cm), whereas P2 had the longest (13.18 cm). Additionally, it can be noted that P3 yielded the heaviest pods at 16.16g when compared to P2, which yielded 14.09 g. Pinching treatments significantly influenced number of days to flowering, with P3 demonstrating the longest duration. Economic analysis was performed for evaluating technical efficiency, facilitating informed and sustainable decisions. Economically, P1 demonstrated superior performance, yielding a higher gross return of NPR 540,808.3, a net return of NPR 418,708.3, and a benefit-cost ratio of 4.43.